Mengukur Wayang Ukur Karya Ki Sukasman - -, Sukirno (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
wayang Purwa, is one kind of puppet that has distinctive characteristics with humans in it a reflection of disposition. Typology thus, hard to find from a variety of ethnic art that is in the archipelago. Distinctive shape with a depiction of what is known than what is seen, is a distinctive characteristic of said visually unique way. In the development of new wayang come with a variety of concepts and styles pakelirannya, not to mention also the doll child. Since the days of Demak until now always appear wanda wanda new in order perfected. One is the "puppet measure/wayang ukur" Ki Sukasman creation of Jogja. The advantages of measuring Ki Sukasman puppet is no loss of character of child. Although if the observed puppet Sukasman Ki gauge is truly the work of individual expression of Ki Sukasman, but wanda perupaan puppet that characterize each of the characers in the puppet is not left, so when I saw a figure measuring puppet, people can still recognize it. Tjis is discussed in this article.Keywords : puppet measure, Ki sukasman